The Influence of Ethical Leadership and Quality of Work Life on Employee Loyalty in MSME Industries in Bandar Lampung City - Yolanda Aisyah Putri; Ribhan Ribhan (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the influence of ethical leadership and quality of work life on employee loyalty in UMKM sector in Bandar Lampung City. Ethical leadership is seen as capable of creating fairness, transparency, and trust within the organization, which can enhance employee loyalty. A good quality of work life, including work-life balance, proper working conditions, and career development opportunities, is also believed to boost employee commitment. This research employed a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 229 respondents, who are employees in UMKM in Bandar Lampung City. The sampling technique used was accidental sampling. The data were analyzed using descriptive statistics and multiple linear regression with the help of IBM SPSS Statistics version 26. The results show that ethical leadership and quality of work life have a positive and significant effect on employee loyalty. These findings suggest that applying ethical leadership values and improving work life quality can be effective strategies for UMKM practitioners to retain loyal and dedicated employees.